Predictors of high-intensity running capacity in collegiate women during a soccer game - McCormack, W. P.; Stout, J. R.; Wells, A. J.; Gonzalez, A. M.; Mangine, G. T.; Fragala, M. S.; Hoffman, J. R. (The Journal of Strength and Conditioning Research, 2014)
The purpose of this investigation was to determine which physiological assessments best predicted high-intensity running (HIR) performance during a women's collegiate soccer game. A secondary purpose was to examine the relationships among physiological performance measures including muscle architecture on soccer performance (distance covered, HIR, and sprints during the game) during a competitive collegiate women's soccer game. Ten National Collegiate Athletic Association (NCAA) Division I women soccer players performed physiological assessments within a 2-week period before a competitive regulation soccer game performed during the spring season. Testing consisted of height, body mass, ultrasound measurement of dominant (DOMleg), and nondominant leg (NDOMleg) vastus lateralis for muscle thickness (MT) and pennation angle (PA), VO2max, running economy, and Wingate anaerobic test (WAnT) for peak power (PP), mean power (MP), and fatigue rate (FR). During the game, distance run, HIR, and sprints were measured using a 10-Hz global positioning system. Stepwise regression revealed that VO2max, dominant leg thickness, and dominant leg PA were the strongest predictors of HIR distance during the game (R = 0.989, SEE = 115.5 m, p = 0.001). VO2max was significantly correlated with total distance run (r = 0.831; p = 0.003), HIR (r = 0.755; p = 0.012), WAnTPP (r = -0.737; p = 0.015), WAnTPP/kg (r = -0.706; p = 0.022), and WAnTFR (r = -0.713; p = 0.021). DOMlegMT was significantly correlated with WAnTFR (r = 0.893; p = 0.001). DOMlegPA was significantly correlated with WAnTFR (r = 0.740; p = 0.023). The NDOMlegPA was significantly correlated to peak running velocity (r = 0.781; p = 0.013) and WAnT MP/kg (r = 0.801; p = 0.01). Results of this study indicate that VO2max and muscle architecture are important characteristics of NCAA Division I women soccer players and may predict HIR distance during a competitive contest.